An Explanation-Based Classroom Response System for Real-Time Analysis of Undergraduate Students’ Natural Language Explanations - Esiason, Jordan; Khare, Priyanka; Aguiar, Claire; Carpenter, Dan; Min, Wookhee; Lee, Seung; Ozogul, Gamze; Zheng, Xiaoying; Lester, James (Proceedings of the AAAI Conference on Artificial Intelligence, 2026)
Effective classroom teaching requires instructors to be responsive to their students, such as by pivoting their lectures in real-time to address common misconceptions that their students may have developed. Classroom response systems such as multiple-choice "clicker" systems are one method by which instructors can gauge their students’ understanding during classroom lectures, but open-ended questions that prompt students to engage in self-explanation are better suited to promoting critical thinking. Additionally, analyzing students’ natural language responses typically requires time-consuming manual analysis, which makes it challenging to implement in a classroom setting. To address this challenge, we present an LLM-driven method for automatically assessing students’ responses and generating an aggregated summary of LLM-based evaluations for their self-explanations during undergraduate classroom lectures. Our approach extracts relevant knowledge components for a given question, tags students’ responses according to whether they correctly address each knowledge component, and generates class-level summaries that highlight common misconceptions and gaps in knowledge to support instructors in pivoting their lectures in real time. We evaluate the system’s effectiveness at these tagging and summarization tasks on data from an undergraduate computer science course, using quantitative and qualitative metrics such as relevance, sufficiency, hallucination rate, and alignment with instructional goals and desired feedback format gathered through instructor interviews. Results suggest that the explanation-based classroom response system can accurately analyze students’ natural language explanations.